Developmental regulation of expression and activity of multiple forms of the Drosophila RAC protein kinase. - Andjelkovic, M.; Jones, P.F.; Grossniklaus, U.; Cron, P.; Schier, A.F.; Dick, M.; Bilbe, G.; Hemmings, B.A. (Journal of Biological Chemistry, 1995)
We have characterized the Drosophila homologue of the proto-oncogenic RAC protein kinase (DRAC-PK). The DRAC-PK gene gives rise to two transcripts with the same coding potential, generated by the use of two different polyadenylation signals. Each transcript encodes two polypeptides because of the presence of a weaker initiator ACG codon, upstream from the major AUG, such that the larger protein contains an N-terminal extension. Like the human isoforms, DRAC-PKs possess a novel signaling region, the pleckstrin homology domain. DRAC-PK proteins have a similar expression pattern, being regulated both maternally and zygotically, and are expressed throughout Drosophila development. Antisera specific for recombinant DRAC-PK and for its C terminus detected two polypeptides of 66 and 85 kDa in Drosophila extracts. The antirecombinant antisera also recognized a polypeptide of 120 kDa from Drosophila, which apparently shared an epitope related to DRAC-PK sequences. The role of p120 appears to be restricted compared with that of DRAC-PK, since it was not detected in larvae or adult flies. There was no spatial restriction of DRAC-PK expression during embryogenesis, suggesting that localized activation might be a regulatory mechanism for its function. DRAC-PK possesses an intrinsic kinase activity that is approximately 8-fold higher in adult flies than in 0-3-h embryos undergoing rapid mitotic cycles.